Yams—Dioscorea spp. - James M. Stephens (EDIS, 2003)
This document provides an overview of yams (genus Dioscorea), detailing their botanical characteristics, uses, and cultivation practices. It distinguishes true yams from sweet potatoes, outlines edible and medicinal species, and describes their growth in tropical and subtropical regions. The article also highlights various yam types and offers guidance on planting and harvesting, particularly in Florida. Original publication date May 1994.